1983
DOI: 10.1002/jcp.1041160312
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast contraction of collagen lattices in vitro: Inhibition by chronic inflammatory cell mediators

Abstract: Fibroblast-populated collagen lattices (FPCL), prepared in petri dishes with serum-containing culture medium and incubated at 37 degrees C, undergo progressive and symmetric contraction (reduction in size) over a period of days. The in vitro contraction process requires viable cells with intact cytoskeletal elements, is associated with cell elongation, and is believed to represent a fibroblast function which also occurs in vivo during wound healing and tissue fibrosis. We report that soluble mediators elaborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(54 citation statements)
references
References 13 publications
1
53
0
Order By: Relevance
“…#P Ͻ 0.01. (9). Taken together, these data suggest that a dynamic, reciprocal relationship exists between epithelial cell migration and ECM fibronectin deposition such that ECM remodeling is downregulated after fibronectinmediated reepithelialization of the airways.…”
Section: Discussionmentioning
confidence: 73%
“…#P Ͻ 0.01. (9). Taken together, these data suggest that a dynamic, reciprocal relationship exists between epithelial cell migration and ECM fibronectin deposition such that ECM remodeling is downregulated after fibronectinmediated reepithelialization of the airways.…”
Section: Discussionmentioning
confidence: 73%
“…PGE is a well-established inhibitor of several fibroblast repair responses, including chemotaxis (18,46), proliferation (47,48), production of extracellular matrix macromolecules (48), and contraction of three-dimensional collagen gels (16,17). The current study evaluated only chemotaxis and contraction, but it seems likely that PGE may also contribute to the reduced proliferation noted in fibroblasts from patients with COPD.…”
Section: Discussionmentioning
confidence: 94%
“…Increased production of PGE 2 , a known inhibitor of both gel contraction and chemotaxis (16)(17)(18), accounts for part of the reduced activity of fibroblasts from subjects with COPD. Consistent with the increased production of PGE, fibroblasts from subjects with COPD have increased expression of COX1 and COX2, two enzymes that regulate the production of prostaglandins in fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The number of human foreskin fibroblasts and 3T3-L1 cells contained within collagen gels, whether in the presence or absence of TGF-, showed no significant change during the course of the Medical Sciences: Montesano (18)(19)(20)(21)(22) have shown that fibroblasts incorporated into three-dimensional collagen gels induce a progressive contraction of the gels and that this phenomenon requires the presence of serum. We have demonstrated here that TGF-pB substitutes for serum in stimulating fibroblast contraction of collagen gels and markedly enhances the contraction normally observed in the presence of serum.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon has been considered as an in vitro equivalent of the connective-tissue contraction that occurs during wound healing and other biological processes (18)(19)(20)(21)(22), and it provides a simple method ofquantitating the contractile ability offibroblasts. Using this model, we have found that TGF-P powerfully enhances the ability of fibroblasts to contract a collagen matrix.…”
mentioning
confidence: 99%